Dark current analysis of germanium-on-insulator vertical p-i-n photodetectors with varying threading dislocation density - Son, Bongkwon (2020)
Dark current characteristics of germanium (Ge) vertical p-i-n photodetectors were studied. Ge photodetectors were demonstrated on the germanium-on-insulator (GOI) platforms realized via direct wafer bonding and layer transfer. GOI platforms with two different threading dislocation densities (TDDs) of 3.2 × 106 cm−2 (low TDD) and 5.2 × 108 cm−2 (high TDD) were varied via furnace annealing in oxygen ambient. An ultra-low dark current density of 1.12 mA/cm2 for epi-Ge photodetectors was obtained for a low TDD Ge photodetector. This is reduced by a factor of 53 in comparison with a high TDD Ge photodetector. A dominant leakage contribution component shifts from bulk leakage to surface leakage as TDD decreases to 3.2 × 106 cm−2, suggesting that advanced surface passivation is required to further reduce the leakage current. Through an activation energy study, it is revealed that a primary bulk leakage mechanism shifts from Shockley–Read–Hall (SRH) leakage to diffusion leakage in a temperature range of 323–353 K. The surface leakage performed with plasma enhanced chemical vapor deposition-deposited SiO2 is governed by SRH and trap-assisted tunneling leakage processes. Two orders of magnitude enhancement in the effective carrier lifetime is observed with the reduction in TDD. This work suggests that bulk leakage current density and effective lifetime analysis provide a better understanding of TDD-dependent dark leakage current study.